Muhammadiyah's Dawah Strategy in Increasing Religious Awareness. - Amin, Muliaty; Hamzah, Andi Abd.; Humaerah, Humaerah (Jurnal Mercusuar, 2021)
This research aims to determine how Muhammadiyah's dakwah strategy can increase religious awareness in Balassuka Village, Gowa Regency, and what factors support or hinder the implementation of Muhammadiyah's dakwah strategy in increasing religious awareness in Balassuka Village, Gowa Regency. The results show that Muhammadiyah's dakwah strategy to increase religious awareness in Balassuka Village, Gowa Regency, is: 1) creating a business venture, 2) conducting religious studies, 3) organizing Baitul Arqam cadres, and 4) forming a jamaah through mutual cooperation. The supporting factors for Muhammadiyah's dakwah strategy in increasing religious awareness are: 1) Muhammadiyah has autonomous organizations, 2) implemented work programs, 3) cooperation between majelis tablig and mubaligh, 4) the existence of a business venture, and 5) government support. The hindering factors are: 1) some people still maintain their ancestral beliefs, and 2) the dakwah materials.